Pola Pertumbuhan dan Faktor Kondisi Ikan Kepar (Belontia hasselti) di Sungai Ambangah Kalimantan Barat - Widadi Padmarsari Soetignya; Mardan Adijaya; Bambang Kurniadi; Marsiana Rida (JURNAL BIOS LOGOS, 2023)
The Malay Combtail fish (Belontia hasselti) is one of the dominant fish species in the Ambangah River that has the potential to be cultivated. This study aimed to determine the growth patterns and condition factor of the Malay Combtail fish (Belontia hasselti) in the Ambangah River, West Kalimantan. Fish samples were taken from May to August 2020 monthly. Parameters measured include total length, weight, sex ratio, and water quality. The results showed that the sex ratio between males and females was balanced (1:1.15). The growth pattern is negative allometric, and the population condition factor of the Malay Combtail fish for males, females, and a combination of both are more than one, which means good, and the magnitude is 1.77; 1.91 and 1.85. The water environmental factors namely temperature, brightness, and dissolved oxygen were still suitable for fish life, while the waters pH was in accordance with its natural condition (peat waters).